Deformation Behavior of Wrought and EBAM Ti-6Al-4V under Scratch Testing; Metals; Vol. 11, iss. 11 - Shugurov A. R. Artur Rubinovich; Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Kazantseva L. M. Lyudmila Mikhaylovna; Martynov S. A. Sergey Aleksandrovich; Bakulin A. V. Aleksandr Viktorovich; Kulkova S. E. Svetlana Evgenjevna (2021, 2021)
Title screen